A study of heat transfer modes in two stages incineration system - 381762 Amirollah Abdul Wahab (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 2004